Editorial – Revista Educação Especial - Mendes, Geovana Mendonça Lunardi; Lockmann, Kamila; Pletsch, Márcia Denise; Schmidt, Carlo; Menezes, Eliana Pereira de; Berni, Clenio Perlin (Revista Educação Especial, 2018)
Editorial - 2018